Firm performance as a determinant of executive compensation in South Africa - Essop, Zahir (My University, 2013)
In line with the Pay-for-Performance model and agency theory this study examines whether executive compensation is reflective of firm performance in South Africa. South Africa presents a unique institutional context. It has mature regulatory institutions but due to socio-economic issues post Apartheid such as income disparities and high unemployment South Africa’s corporate governance system is evolving from a shareholder to a stakeholder governance system. The results of this study thus yield new insights for executive compensation research. Executive compensation data for the Johannesburg Securities Exchange (JSE) Top 40 firms over a five year period was compiled. A comprehensive measure of executive compensation including salaries, benefits, bonuses, shares and share options was used. Both market and accounting based measures of firm performance were used. These included Total Shareholder Return and Return on Assets. A panel regression analysis detected a moderate positive pay - performance relationship in South Africa. The results of this study suggest that the Pay-for-Performance or agency model with its exclusive focus on aligning executive compensation to shareholder interests has to be extended to take into account other stakeholder interests. It is only then that the model can be used to explain executive compensation levels in countries with stakeholder governance systems.
MBA thesis
Keywords: Executive compensation; Salaries; Performance management